Evaluation of the Language Communicational Skills of Persons With Broca’s Aphasia as a Concomitance from Cerebrovascular Insult - Todorov, Ilija; Trajkovski, Vladimir (My University, 2011)
Persons with Broca’s aphasia socialize in society much faster, because of the early rehabilitation treatment using the speech therapy. In the beginning of the illness, the voice production is arduous and the speech is with variable prosody. The patient expresses himself exceptionally with nouns and working verbs, also using mimics and gestures. The main purpose of the research is the evaluation of the communicational language skills of persons with Broca’s aphasia, even in the acuteness of the illness. The goal is also to examine and establish the opinion of persons with Broca’s aphasia, their family members and medical staff regarding the use of early rehabilitation treatment with speech therapy. The basic tasks of this research are to determine whether the disturbance of verbal interaction is often followed with speech apraxia and agrammatism among the persons suffering from Broca’s aphasia. Two types of examinees are included in the research. The survey was conducted in Skopje and in a period of three months. The data gained from the research are grouped, tabulated, processed and graphically shown using the program Microsoft Office Excel 2003. The differecnces in the data of the examinees is analyzed with Chi square test with level of significance р<0.05. From the analyzis and interpretation of the results we can see that persons with Broca’s aphasia, although produce incomplete sentences, they verbalise sentences with content which are informative for their interlocutor and the auditory understending is less demaged than the expressive funcion of the speech. In conclusion, the study found that early rehabilitation treatment using speech therapy for persons with Broca’s aphasia resulted in faster improvements and better capabilities for speech-language communicational skills.
Keywords: communication assessment, cerebrovacular insult, Broca’s aphasia, speech-language skills, speech therapy treatment